Cervical cancer mortality by neighbourhood income in urban Canada from 1971 to 1996 - Ng, Edward (Canadian Medical Association, 2004)
BACKGROUND: The reduction of socioeconomic inequalities in health is an explicit objective of health policy in Canada, yet rates of death from cervical cancer are known to be higher among women of low socioeconomic status than among those of higher socioeconomic status. To evaluate progress toward the World Health Organization's goal of “Health for All,” we examined whether income-related differentials in cervical cancer mortality diminished from 1971 to 1996. METHODS: Death registration data for Canada's census metropolitan areas in 1971, 1986, 1991 and 1996 were assigned to census tracts through postal code, and the tracts were in turn assigned to income quintiles based on their proportion of the population below the Statistics Canada low-income cutoff values. We compared age-standardized death rates (using the 1966 world population standard) in the female population (excluding those in institutions) across the 5 income quintiles and calculated interquintile rate ratios (poorest over richest) and interquintile rate differences (poorest minus richest). RESULTS: From 1971 to 1996, the overall age-standardized cervical cancer death rate per 100 000 women (and 95% confidence interval) declined from 5.0 (4.5–5.6) to 1.9 (1.7–2.1), the interquintile rate ratio diminished from 2.7 (1.8–4.2) to 1.7 (1.1– 2.6), and the interquintile rate difference decreased from 4.6 (2.8– 6.4) to 1.1 (0.2–1.9). INTERPRETATION: The income-related disparity in rates of death from cervical cancer as measured by rate ratios and rate differences diminished markedly in urban Canada from 1971 to 1996. Among the numerous factors that may have contributed to the decline (including decline in fertility and improvement in diet), one important factor was probably the implementation of effective screening programs.